Prevalence of Trichomoniasis in Women with HIV in Sragen District - Hanny Endah Setiowati; Adhi Kumoro setya (GLOBAL HEALTH SCIENCE GROUP, 2025)
Trichomonas vaginalis infection remains one of the most common non-viral sexually transmitted infections (STIs) globally, despite being one of the most easily treatable STIs. This study aims to determine the prevalence and risk factors associated with trichomoniasis among HIV-positive women in Sragen Regency. A total of 30 HIV-diagnosed women from the Sehat Panghuripan Sukowati Foundation in Sragen, aged 15–49 years, participated in this study. Respondents completed a questionnaire and underwent urinalysis at Prodia Medical Laboratory, Sragen. The presence of Trichomonas vaginalis infection was evaluated using a wet mount microscopic method. Clinical features were collected through structured questionnaires administered to each participant. Result: The findings revealed the prevalence of Trichomoniasis among HIV-positive women, indicating that Trichomoniasis can increase HIV viral load in vaginal fluid, potentially heightening the risk of HIV transmission. The study demonstrated a higher infection rate in women with a history of sexually transmitted infections (HIV), particularly those over 30 years of age. Most participants were housewives with a single sexual partner, reported no vaginal discharge complaints, but had experienced abnormal vaginal secretions in the past. The recorded prevalence of Trichomoniasis in this study was 10% (3 out of 30 samples)